Pengembangan e-LKPD Terintegrasi STEM-PjBL pada Materi Asam Basa Kelas XI SMA Menggunakan Flip PDF Proffesional Software - Yogi Febrianto; Desy Kurniawati (Universitas Negeri Padang, 2023)
Variation of learning media is e-LKPD (electronic Student Worksheet) with Flip PDF Professional. Making e-LKPD is an effort to improve critical thinking skills, understanding concepts and linking the acquired knowledge to real life through integrated learning. The approach that can be used is STEM (Science, Technology, Engineering and Mathematics) which is usually followed by several learning models, one of which is PjBL (Project Based Learning). The purpose of this study was to develop an integrated STEM-PjBL e-LKPD on acid-base material for class XI SMA. This type of research is Research and Development which uses a 4-D development model, define, design, develop, and disseminate. The data analysis used is validity and practicality. The data analysis technique uses Aiken'sV to analyze the validity of the data and Kappa Aiken'sV Cohen to analyze the practicality of the data. The average Aikken'sV validity test scale is 0.85 with a very high validity category. Aikken'sV scale. The practical kappa moment of the teacher's practicality sheet is 0.90 in the very high category and from the student's practicality sheet, 0.82 is in the high category. This shows that the integrated STEM PjBL e-LKPD on acid-base material for class XI SMA which was developed is valid and practical as a learning media.